2013
DOI: 10.1007/s10495-013-0858-y
|View full text |Cite
|
Sign up to set email alerts
|

Reduced glutathione export during programmed cell death of Neurospora crassa

Abstract: In a previous study, we demonstrated that staurosporine (STS) induces programmed cell death (PCD) in the fungus Neurospora crassa and that glutathione has the capability of inhibiting both STS-induced reactive oxygen species (ROS) formation and cell death. Here, we further investigated the role of glutathione in STS-induced PCD in N. crassa and observed an efflux of reduced glutathione (GSH) together with a change in the cell internal redox state to a more oxidative environment. This event was also observed wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
20
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 32 publications
1
20
0
Order By: Relevance
“…Other antifungals also induce glutathione enzymes to reduce intracellular ROS levels in N. crassa . 40 …”
Section: Resultsmentioning
confidence: 99%
“…Other antifungals also induce glutathione enzymes to reduce intracellular ROS levels in N. crassa . 40 …”
Section: Resultsmentioning
confidence: 99%
“…Staurosporine induces cell death in N. crassa accompanied by typical features like loss of viability, DNA fragmentation, ROS production, and GSH export (Castro et al 2010; Fernandes et al 2013). Previously, by screening strains from the N. crassa deletion collection (Colot et al 2006) for sensitivity to staurosporine, we observed that a strain lacking NCU09974 was highly susceptible to the drug (Fernandes et al 2011).…”
Section: Resultsmentioning
confidence: 99%
“…In N. crassa , cell death can be triggered genetically through the fusion of hyphae or germlings of two incompatible individuals at het loci (Hutchison et al 2009, 2012) or induced with phytosphingosine (Castro et al 2008; Fernandes et al 2013; Videira et al 2009), staurosporine (Castro et al 2010; Fernandes et al 2011, 2013), hydrogen peroxide (Castro et al 2008), chitosan (Palma-Guerrero et al 2009), or PAF26 (Munoz et al 2012). It can also be stimulated through ectopic expression of the phcA gene from Pseudomonas syringae (Wichmann et al 2008) or by a combined stimulus of heat shock (45°) with 2-deoxyglucose-induced glucose deprivation (Plesofsky et al 2008; Plesofsky-Vig and Brambl 1995).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Glutathione reductase (GR) transfers GSSG to GSH, while GPx transfers GSH to GSSG in filamentous fungi (Bai et al, 2003;Fernandes et al, 2013;Viefhues et al, 2014). Glutathione-S-transferase (GST) and thioredoxin peroxidase (TPx) augments GPx activity (Mhamdi et al, 2010).…”
Section: Changed Redox State By Gpx Knock-down Has Effect On Ros Relamentioning
confidence: 99%